Pembinaan Klub Bulutangkis di Kabupaten Blora - Fauzi, Muhammad Muhammad; Raharjo, Hermawan Pamot (Universitas Negeri Semarang, 2023)
The problems in this study are known from the results of initial observations, namely; There were no medals won in the PORPROV and KEJURPROV Badminton championships, the championships in Blora Regency were always dominated by that club alone. with the continuity stake approach model, the data sources of this research are administrators, coaches, athletes, athletes' parents. Data collection techniques are observation, interviews, documentation. The results of the study, (1) antecedents, planning for coaching at PB Jaya Mustika to advance badminton in Blora Regency, training and fostering athletes to get maximum performance. PB Jaya Mustika's coaching planning emphasizes on the mental development of athletes, PB Mustika Raya distinguishes between coaching plans for novice athletes and achievement athletes, PB Cepu Junior holds training matches, facilities and infrastructure that PB Jaya Mustika is good and adequate, there are equipment, PB Mustika Raya is quite good , PB Cepu Junior still has many shortcomings and no equipment, the reception of athletes and coaches in the three clubs is still simple and appointed by the management, the source of funds is from athlete fees, (2) Transaction, the implementation of the training program has not been going well because there is no training program. (3) Outcomes, the achievements of athletes in Blora Regency have not been maximized..